Spatial analysis of changes and anomalies of intense rainfalls in Hungary - Gergely Jakab; Tibor Bíró; Zoltán Kovács; Ádám Papp; Ninsawat Sarawut; Zoltán Szalai; Balázs Madarász; Szilárd Szabó (Hungarian Geographical Bulletin, 2019)
Extreme precipitation events can trigger flash flood, mass movements, pluvial flood and accelerated soil erosion. As soil structures are highly degraded due to intensive improper cultivation water infiltration can considerably decrease during the vegetation period. Additional changes in canopy coverage on the soil surface cause relevant variability in infiltration and hence vulnerability against runoff related disasters. Most researchers agree that the frequency of extreme precipitations increases, however, in the Carpathian Basin the uncertainties are quite high. This study aims to compare daily maximum mean precipitation amounts (MMPA) predicted by the Goda-method for June and August as the most probable months of extremities. We used the CarpatClim database as input and predicted MMPAs for two periods, 1960–1985 and 1986–2010. The Goda-method uses monthly data and calculates daily results on given probability. A general increase was found between the first and second half of the period regarding daily maximum precipitation amount in both investigated months. For August the 1-day precipitation amount increased from 56.1 mm to 61.8 mm, whereas 6-days amount from 93.8 mm to 103.2 mm at 1 per cent probability (r = 0.53; p < 0.001). Beyond this change, relevant spatial differences were found. Comparing the macro regions plains had lower increase compared to the mountains, whereas the highest increase was at the. The most endangered location is the southern part of the Transdanubian Hills where parallel with the intensive increase in MMPA both in June and August the environmental conditions such as loose parent material and the high percentage of crop fields also emphasize the potential hazard.